A QUALITATIVE STUDY OF TEACHERS’ PERCEPTIONS TOWARDS THE ASSESSMENT REFORM IN PRIMARY SCHOOLS - Shanusi Ahmad; Nor Hasnida Che Md Ghazali; Mohd Nazir Md Zabit, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
The present paper is a qualitative case study of exploring the perceptions of assessment reform in primary schools in Malaysia. It is to explore the approaches developed by schools in response to the National Education Assessment System (NEAS) and to explore the factors which affect the implementation of NEAS. The participants of the study are teachers and the head teachers. Data was collected using semi-structured interviews and observations. Results of data analysis revealed that the SAGA Primary School was found to be representing a school that successful in implementing the NEAS. It clearly shows that there is a true spirit of teamwork, a good leadership and good beliefs among teachers. All the approaches were meant to help in achieving the objectives in NEAS implementation. The factors which affect the implementation of the NEAS for both schools are great relationships between staffs, leadership and positive beliefs in teachers.